PENERAPAN WATER CHILLER DAN BOX FREEZER UNTUK PENDINGINAN DAN PENYIMPANAN PURE MANGGA - Setiawan, Aa; Wardika, Wardika; Kurniawan, Yudhy (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
There are many processed mangoes, one of which is processed into mango pure. Pure is mango fruit pulp which is processed through pasteurization technology or a cooking process by heating it to a high temperature reaching 70-80 oC. A tool is needed to cool the pure and at the same time store it in one place. The aim of this community service program is to increase partner empowerment and increase the types of processed mango products. The methods in this program are observation, identifying partner problems, making tools, testing, and assisting in using the tools. This activity was successfully carried out as seen from the tool's ability to reduce the pure temperature from 70 oC to 25 oC in 4 hours 30 minutes